Comparative Analysis of Financial Performance in Manufacturing Companies Listed on The Indonesian and Malaysian Stock Exchanges in 2023 - Hardiyanti, Chichi; Aty Herawati (Dinasti International Journal of Digital Business Management, 2024)
Financial Performance is a series of financial activities in a certain period which are reported in financial reports including the profit and loss report and balance sheet. The aim of this research is to find out the comparison of the financial performance of manufacturing companies on the Indonesia Stock Exchange (BEI) and the Malaysia Stock Exchange in 2023. The financial ratios used in this research are Return on Assets (ROA), Debt to Equity Ratio ( DER), Current Ratio (CR), Total Assets Turnover (TATO), and Price Earnings Rasio (PER).  The statistical analysis used in this research is the paired sample t-test and the Wilcoxon signed rank test. The results of previous research show that there is an influence on all the financial ratios studied.